The effects of health-preserving sports on the treatment of COVID-19: A protocol for systematic review. Issue 2 (15th January 2021) - Ji, Yu; Qiu, Guorong; Song, Dandan; Liu, Hezhi; Chen, Li
Abstract: Background: From the end of 2019, COVID-19 has become a global epidemic, threatening the physical and mental health of everyone. How to effectively prevent and treat COVID-19 is concerned. Some studies have shown that Health-Preserving Sports plays an active role in the prognosis treatment of COVID-19. Therefore, this study aims to provide a method to assess the efficacy and safety of Health-Preserving Sports for the prognosis of COVID-19. Methods: This protocol is guided by the Preferred Reporting Items for Systematic Reviews. The following electronic databases will be searched: PubMed, the Cochrane Central Register of Controlled Trials, Excerpta Medica Database, MEDLINE, Web of Science, China National Knowledge Infrastructure Database, Chinese Biomedical Literature Database, China Science and Technology Journal Database, and Wan-Fang Database. We will be screened for data extraction and analysis, to summarize the therapeutic effect of Health-Preserving Sports on the treatment of COVID-19. Result: This study will provide a reliable evidence for the treatment of COVID-19 by Health-Preserving Sports. Conclusion: To provide a method to assess the efficacy and safety of Health-Preserving Sports for the prognosis of COVID-19, and guide future researches. PROSPERO registration number: CRD42020219526.